Detection of carbapenemase-producing Enterobacterales by means of matrix-assisted laser desorption ionization time-of-flight mass spectrometry with ertapenem susceptibility-testing disks as source of carbapenem substrate - Shaidullina, Elvira R.; Romanov, Andrey V.; Skleenova, Elena Y.; Sheck, Eugene A.; Sukhorukova, Marina V.; Kozlov, Roman S.; Edelstein, Mikhail V. (Frontiers in Microbiology, 2022)
MALDI-TOF mass spectrometry has become widely used in clinical microbiology and has proved highly accurate for detection of carbapenemases in Gram-negative bacteria. However, the use of carbapenem-hydrolysis assays in routine diagnostics is hampered by the need for antibiotic substances and for making their fresh solutions each time an assay is conducted. Here, we evaluated the use of commercial antibiotic susceptibility-testing disks as source of ertapenem substrate in MALDI-TOF MS-based assay for detection of carbapenemase-producing Enterobacterales (CPE). The assay was validated on 48 CPE isolates of 8 different species expressing NDM-, VIM-, KPC- and OXA-48-type carbapenemases and exhibiting various levels of resistance to carbapenems (MIC range: 0.25– > 32 mg/l), as well as on 48 carbapenemase-non-producing isolates. The assay conditions were optimized as follows: 10-μl loopful of bacterial colonies was suspended in 150 μl 0.01 M Na-PBS buffer, pH 7.4, a 10 μg ertapenem susceptibility-testing disk was immersed in the suspension and incubated 3 h at 35°C, after which supernatant was obtained by centrifugation and applied on a target plate with alpha-cyano-4-hydroxycinnamic acid matrix. Mass spectra were analyzed between 440 and 560 m/z. Carbapenemase activity was detected in all tested CPE isolates by the appearance of m/z peaks corresponding to ertapenem hydrolysis products: [Mh + H]+:494.2, [Mh + Na]+:516.2, [Mh + 2Na]+:538.2, [Mh/d + H]+:450.2, [Mh/d + Na]+:472.2, and simultaneous decrease or loss of peaks of intact antibiotic: [M + H]+:476.2, [M + Na]+:498.1, [M + 2Na]+:520.1. No hydrolysis peaks or loss of intact ertapenem peaks were observed for carbapenemase-negative strains. We therefore report the development of a sensitive, specific and cost-effective MALDI-TOF MS-based assay for detection of CPE, which makes use of antibiotic disks readily available in most laboratories.